Disciplinary Conquest - Salvatore, Ricardo (Duke University Press, 2016)
In DISCIPLINARY CONQUEST, Ricardo Salvatore argues that the foundation of the discipline of Latin American studies, pioneered between 1900 and 1945, was linked to the United States's business and financial interests and informal imperialism. In contrast, the consolidation of Latin American studies has traditionally been placed in the 1960s, as a reaction to the Cuban Revolution. Focusing on five representative U.S. scholars of South America-historian Clarence Haring, geographer Isaiah Bowman, political scientist Leo Rowe, sociologist Edward Ross, and archaeologist Hiram Bingham -- Salvatore demonstrates how their search for comprehensive knowledge about South America can be understood as a contribution to hemispheric hegemony, an intellectual conquest of the region. U.S. economic leaders, diplomats, and foreign-policy experts needed knowledge about the region to expand investment and trade, as well as the U.S.'s international influence